2021
DOI: 10.3389/fimmu.2021.638020
|View full text |Cite
|
Sign up to set email alerts
|

The First Contact of Human Dendritic Cells With Trypanosoma cruzi Reveals Response to Virus as an Unexplored Central Pathway

Abstract: Chagas disease is a debilitating and neglected disease caused by the protozoan Trypanosoma cruzi. Soon after infection, interactions among T. cruzi and host innate immunity cells can drive/contribute to disease outcome. Dendritic cells (DCs), present in all tissues, are one of the first immune cells to interact with Trypanosoma cruzi metacyclic trypomastigotes. Elucidating the immunological events triggered immediately after parasite-human DCs encounter may aid in understanding the role of DCs in the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 133 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…Therefore, by intervening in this pathway, it is possible to eliminate pathogens infected cells and delay the progression of CCC. What’s more, Leukocyte transendothelial migration [ 39 ], Chemokine signaling pathway [ 40 ] and PI3K−Akt signaling pathway [ 41 ] may also be key pathways to the regulation of CCC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, by intervening in this pathway, it is possible to eliminate pathogens infected cells and delay the progression of CCC. What’s more, Leukocyte transendothelial migration [ 39 ], Chemokine signaling pathway [ 40 ] and PI3K−Akt signaling pathway [ 41 ] may also be key pathways to the regulation of CCC.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental murine models, it has been shown that IFN-I increases susceptibility to infection in scenarios where parasite loads are high, since they impact negatively on production of IFN-γ, limiting infection [ 43 ]. Recently, an increase in the expression of the antiviral response, which includes the production of IFN-I, in human dendritic cells after contact with metacyclic trypomastigotes of T. cruzi has been demonstrated, indicating the importance of this pathway during the first moments of infection [ 44 ]. In line with our results, adenostemmoic acid B has recently been shown to inhibit iNOS expression and NO production in vitro [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being non-specific for T. cruzi, this protection was truly mediated by the BV because all animals of the sham vaccinated group injected with PBS died before 35 d.p.i., suggesting that innate immune mechanisms triggered by BV are beneficial to partially protect against T. cruzi. Recently, it has been reported that a virus-like infection response is the most up-regulated pathway after the interaction between dendritic cells and T. cruzi 7 . Knowing that wild type BV can induce innate immune responses with production of IFN-α and IFN-γ, the partial protection in our vaccination protocol by wild type BV could be mediated by stimulation of the innate immunity, in a virus-like response.…”
Section: Discussionmentioning
confidence: 99%
“…The precise immune mechanisms involved in protection against T. cruzi are still unclear, but several studies have demonstrated that an effective immune response against T. cruzi should have a Th1 profile, including both humoral and cellular responses, with gamma interferon (IFNɣ) as the major cytokine promoting the activity of phagocytes, T helper cells (CD4+), and cytotoxic T lymphocytes (CD8+) 5 . Furthermore, despite the incomplete understanding of the shape of a fully protective immunity against T. cruzi, there are key cells and components of the innate immune response (macrophages, DCs, NK, TLRs, NODs and cytokines) that should be activated to favor an adequate immune profile that eventually leads to an anti-T. cruzi response 6,7 . Another concern for T. cruzi vaccine development is the adequate selection of the antigens.…”
Section: Introductionmentioning
confidence: 99%